Short-term functional results of surgical management of fractures of olecranon process of ulna by locking hook plate - Lingayat, Maruti B.; Patel, Altamash; Thorat, Chandrakant R. (International Journal of Research in Orthopaedics, 2021)
Background: The aim was to study functional results of fixation of fractures of olecranon process of ulna by locking hook plate. Methods: The study was conducted on 30 patients who underwent fixation of olecranon fracture by locking hook plate in department of orthopaedics, GMCH Aurangabad from September 2018 to September 2020. Patients were assessed functionally using Mayo elbow performance score and radiologically using serial follow up radiographs of elbow. Results: At 2 year follow up of 30 patients of all types of olecranon fracture treated by locking hook plate, no patient had evidence of non-union or loss of reduction or any other major complications. In our study 21 patients (70%) showed excellent results, 6 patients (20%) showed good results and 3 patients (10%) showed fair results. None of the patients in our study showed poor results. 3 patients (10%) had superficial infection which were treated by adequate antibiotics after doing culture and sensitivity testing and 4 patients (13.33%) had symptomatic metal prominence which underwent implant removal after union of fracture. Conclusions: Fixation of all types of fractures of olecranon by locking hook plate is good alternative to other methods of fixation like tension band wiring, intramedullary fixation using screw tension band wiring which are used only in selected cases. In our study we conclude that locking hook plate is excellent modality of treatment for all types of fractures of olecranon, it gives excellent functional and radiological outcome with minimal complication and stable fixation of all types of fractures including transverse as well as comminuted fractures.